Capacitive catalytic electrode for selectively removing copper ions as well as preparation method and application of capacitive catalytic electrode
By preparing MoS2/FeS or MoS2/WO3 nanoheterojunction on porous carbon electrodes, the electrode meter interface is regulated, and the coupling between electrosorption and photo/electrocatalysis is achieved, the problem of low copper ion removal efficiency in the prior art is solved, and the realization of the realization of the electrode meter interface is achieved. Low energy consumption and high selective removal effect.
Patent Information
- Application Number
- CN202411241815.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-05
AI Technical Summary
When existing electrochemical technology treats complex industrial wastewater, especially copper-containing wastewater, it is difficult to achieve low energy consumption and selective removal of copper ions. The electrode function is single, making it difficult to achieve selective separation or removal of specific ions, making it a heavy metal wastewater. Technical bottlenecks in deep processing and resource utilization.
The hydrothermal method is used to prepare porous carbon electrode modified with MoS2/FeS or MoS2/WO3 nanoheterojunction. By regulating the electrode meter interface, the in-situ coupling between electrosorption and photo/electrocatalytic process is realized, thereby enhancing the conductivity and specific surface area of the electrode and photo/electrochemical activity to achieve selective removal of copper ions.
It realizes low energy consumption and high selectivity removal of copper ions, improves the multi-technical coupling efficiency of electrodes, and can effectively remove copper ions in complex wastewater and achieve their enrichment or recovery.
Smart Images

Figure CN119191494A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of wastewater treatment, in particular to a capacitive catalytic electrode for selectively removing copper ions and a preparation method and application thereof. Background Art
[0002] Copper ion (Cu 2+ ) is a common heavy metal pollutant in industrial wastewater such as electroplating, smelting, and circuit board printing in my country. It has serious ecological toxicity and often requires deep treatment by physical / chemical methods (such as chemical precipitation, physical adsorption, etc.) to achieve higher emission or reuse standards. At the same time, as an important strategic resource, the effective enrichment and recovery of copper is of great significance to promoting my country's carbon emission reduction process.
[0003] At present, green electrochemical technology based on electrosorption and electroreduction has been used in Cu 2+ However, the actual copper-containing industrial wastewater is often complex in composition. The presence of common divalent coexisting cations such as nickel will cause the existing electrodeposition or capacitive deionization system to be 2+ The removal efficiency drops sharply. How to achieve Cu 2+ Low energy consumption and selective removal are one of the technical bottlenecks faced by the current electrochemical technology towards refined development, and are also an effective strategy to improve the enrichment and recovery efficiency of copper resources.
[0004] With the help of a weak electric field below 1.5V, charged ions can be reversibly adsorbed on the electrode surface, thus avoiding the high electrical energy of traditional electrochemical oxidation or reduction processes.
[0005] With the continuous improvement of the theoretical system of electrosorption, pseudocapacitive electrode materials modified with semiconductor materials have been widely studied and applied in improving the ion removal rate. However, most of the existing capacitor electrodes focus on the optimization of adsorption performance and pseudocapacitive performance. On the one hand, the electrode surface interface action mechanism is single, resulting in single electrode function, limited technical integration and coupling efficiency within the electrochemical system, and low pollution control efficiency; on the other hand, facing the new water treatment needs of refinement and resource utilization, the existing capacitor electrodes are often difficult to achieve the selective separation or removal of specific ions, which has become a technical bottleneck for low-energy electrochemical technology in the actual deep treatment and resource utilization of heavy metal wastewater.
[0006] Currently, the research on improving the capacitance, photo / electrocatalytic activity and selectivity simultaneously through electrode surface interface regulation is still in its infancy. The difficulty lies in the balance and synergy between electrode surface interface regulation and double-layer electroadsorption, pseudocapacitive redox and photo / electrocatalysis. Summary of the invention
[0007] The present invention aims to provide a capacitive catalytic electrode for selective removal of copper ions, and a preparation method and application thereof, so as to simultaneously improve its capacitance, photo / electrocatalytic activity and selectivity by regulating the electrode surface interface.
[0008] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing a capacitive catalytic electrode for selective removal of copper ions, comprising the following steps:
[0009] S1: dissolving ammonium molybdate tetrahydrate, thiourea, urea and tungstate or ferrous salt in water, adjusting the solution pH to 1.0-3.0, then adding sodium sulfate and stirring to obtain a composite catalytic component precursor solution;
[0010] S2: Immerse the porous carbon substrate in the composite catalyst component precursor solution, and then heat the composite catalyst component precursor solution at a temperature not exceeding 5°C / min. -1 The temperature is raised to 180-220° C. at a heating rate of 1000 ℃ and kept at this temperature for 12-14 hours. After cooling, the porous carbon substrate is taken out and cleaned to obtain the capacitive catalytic electrode.
[0011] As a further optimization of the above technical solution: in the composite catalytic component precursor solution, the atomic molar ratio of Mo:W is 7:0.5-5.0, or the atomic molar ratio of Mo:Fe is 1:0.1-1.0.
[0012] As a further optimization of the above technical solution: the tungstate is sodium tungstate or sodium tungstate hydrate, and the ferrous salt is ferrous sulfate or ferrous sulfate hydrate.
[0013] As a further optimization of the above technical solution: in step S1, by dropping 2.0 mol L -1 The pH of the solution was adjusted to 1.0-3.0 with sulfuric acid.
[0014] As a further optimization of the above technical solution: the porous carbon substrate is pretreated and then immersed in the composite catalytic component precursor solution. The pretreatment process is specifically as follows: the porous carbon substrate is sequentially cleaned and dried in acetone, anhydrous ethanol and ultrapure water, and cut into a target size.
[0015] As a further optimization of the above technical solution: the porous carbon substrate is graphite felt, activated carbon felt, carbon fiber cloth or activated carbon particles.
[0016] As a further optimization of the above technical solution: the porous carbon substrate is a two-dimensional or three-dimensional carbon material with capacitive properties.
[0017] A capacitive catalytic electrode for selective removal of copper ions is prepared by any of the above methods. The capacitive catalytic electrode is a MoS2 / FeS / GF electrode or a MoS2 / WO3 / GF electrode.
[0018] The invention discloses an application of a capacitive catalytic electrode for selectively removing copper ions in treating industrial sewage, wherein the industrial sewage contains copper and nickel.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention uses a hydrothermal method to achieve the construction, loading and electrode surface interface regulation of MoS2 nanoheterojunction in one step, and in situ couples the electrosorption and photo / electrocatalytic processes through the optimization of the composite ratio to obtain a Cu-containing nanoheterojunction with capacitance, photo / electrocatalytic activity and Cu-containing nanoheterojunction. 2+ Selective integrated electrode, the modified electrode can be directly used in the electrochemical system to achieve in-situ coupling of electrosorption and photo / electrocatalysis process, to achieve Cu 2+ The purpose of low energy consumption and high selectivity removal.
[0021] In the modification process of the electrode of the present invention, the nano-heterojunction of MoS2 and transition metal sulfide or oxide such as FeS, WO3 is constructed and regulated on the porous carbon surface, so that the electrode has excellent conductivity, large specific surface area and photo / electrochemical activity, thereby achieving effective synergy of its surface interface double electric layer electrosorption, pseudocapacitive redox and photo / electrocatalysis process, and improving the electrode's Cu 2+ At the same time, based on the "soft and hard acid-base" theory, the S element at specific active sites in the nano-heterojunction is used to strengthen the electrode's electrosorption, mass transfer and storage properties. 2+ The selectivity of the electrode is achieved by utilizing the efficient integration and in-situ coupling of multiple mechanisms at its surface interface, which makes it have excellent capacitance, photo / electrocatalytic activity and Cu 2+ Selective removal capability. This electrode can be used in low-energy electrochemical systems to improve the efficiency of multi-technical coupling and achieve Cu removal in water 2+ Enhanced removal and selective separation, enrichment or recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Cyclic voltammetry curves of MoS2 / FeS / GF(0.1) and unmodified GF electrodes (the inset is the constant current charge-discharge curve of MoS2 / FeS / GF(0.1));
[0023] Figure 2 The MoS2 / FeS / GF electrodes with different composite ratios react with Cu in water 2+ Selective removal performance;
[0024] Figure 3 Cyclic voltammetry curves of MoS2 / WO3 / GF(2.5) and unmodified GF electrodes (Inset (a) is the constant current charge-discharge curve of MoS2 / WO3 / GF(2.5); Inset (b) is the light absorption performance of the catalytic active component);
[0025] Figure 4 For MoS2 / WO3 / GF(2.5) electrode on Ni 2+ Selective removal of Cu in water under interference conditions 2+ performance;
[0026] Figure 5 Removal of Cu in water by MoS2 / WO3 / GF electrodes with different composite ratios 2+ performance. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.
[0028] The present invention discloses a method for preparing a capacitive catalytic electrode for selective removal of copper ions, comprising the following steps:
[0029] S1: dissolving ammonium molybdate tetrahydrate, thiourea, urea and tungstate or ferrous salt in water, adjusting the solution pH to 1.0-3.0, then adding sodium sulfate and stirring to obtain a composite catalytic component precursor solution;
[0030] Specifically, using water as solvent, add ammonium molybdate tetrahydrate, thiourea and urea to water in a molar ratio of 1:35:4, stir until dissolved, and obtain a colorless transparent solution. Add a certain amount of tungstate or ferrous salt as a transition metal oxide or sulfide precursor, tungstate is a soluble tungstate, including but not limited to sodium tungstate or sodium tungstate hydrate, ferrous salt is a soluble ferrous salt, including but not limited to ferrous sulfate or ferrous sulfate hydrate, control the atomic molar ratio of Mo:W to 7:0.5-5.0, and the atomic molar ratio of Mo:Fe to 1:0.1-1.0, and stir until dissolved. Slowly drop 2.0 mol·L -1 Sulfuric acid and stirred vigorously, and the pH of the solution was adjusted to 1.0-3.0. During this period, precipitation was produced or the color of the solution changed. A certain amount of anhydrous sodium sulfate was added to make the concentration of sodium sulfate in the solution 0.5 mol·L -1 , and stir for more than 10 minutes to obtain a composite catalytic component precursor solution. S2: Immerse the porous carbon substrate in the composite catalyst component precursor solution, and then heat the composite catalyst component precursor solution at a temperature not exceeding 5°C / min. -1 The temperature is raised to 180-220° C. at a heating rate of 10000 ℃, kept at the temperature for 12-14 hours, and after cooling, the porous carbon substrate is taken out and washed to obtain the capacitive catalytic electrode;
[0031] The porous carbon substrate is pretreated before being immersed in the composite catalytic component precursor solution. The pretreatment process is as follows: the porous carbon substrate is washed and dried in acetone, anhydrous ethanol and ultrapure water in sequence, and cut to a target size; the selected porous carbon substrate is a two-dimensional or three-dimensional carbon material with capacitive properties, including but not limited to a porous carbon substrate such as graphite felt, activated carbon felt, carbon fiber cloth or activated carbon particles;
[0032] The composite catalytic component precursor solution prepared above was transferred to a polytetrafluoroethylene reaction tank, and the pretreated porous carbon substrate was placed on the wall to make it completely immersed in the composite catalytic component precursor solution; the reaction tank was sealed in a stainless steel high-pressure reactor, and the reaction was carried out at 200°C for 12-14h, with a heating rate not exceeding 5°C·min -1 After natural cooling, the porous carbon substrate is taken out and washed with ultrapure water until no solid falls off the surface to obtain an integrated capacitive catalytic electrode, which can be used directly or stored under wet conditions.
[0033] The present invention also discloses a capacitive catalytic electrode for selective removal of copper ions, wherein the capacitive catalytic electrode is a MoS2 / FeS / GF electrode or a MoS2 / WO3 / GF electrode. The present invention also discloses the use of the capacitive catalytic electrode for selective removal of copper ions in treating industrial sewage, wherein the industrial sewage is industrial sewage containing copper and nickel. Specifically, when treating industrial sewage, the catalytic electrode is used in capacitive deionization, photo / electrocatalysis and its coupling system to improve the selective removal, separation or enrichment, and recovery rate of copper ions in water.
[0034] Example 1: Preparation of MoS2 / FeS / GF electrode
[0035] The MoS2 / FeS / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:Fe (the same below) is 1:0.1. The specific preparation method is as follows:
[0036] S1: Add 0.278g of FeSO4·7H2O and 1.77g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 3.81g CN2H4S and 0.35g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0037] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and clean them by ultrasonic cleaning for 10 min, and dry them in air at 60 °C to complete the pretreatment of GF;
[0038] The composite catalytic component precursor solution obtained in step S1 was transferred to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and a piece of pretreated GF was placed against the wall; the reactor was sealed and placed in an oven at 5°C·min -1 The temperature was raised to 200°C at a heating rate of 1.50 °C and maintained for 12 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / FeS / GF electrode, which was recorded as MoS2 / FeS / GF (0.1).
[0039] Example 2: Preparation of MoS2 / FeS / GF electrode
[0040] The MoS2 / FeS / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:Fe is 1:0.5. The preparation method is as follows:
[0041] S1: Add 1.390g of FeSO4·7H2O and 1.77g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 3.81g CN2H4S and 0.35g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0042] The other steps are the same as those in Example 1. After naturally cooling to room temperature, the GF after the reaction in the reactor is taken out from the reactor, and the excess catalytic components on the surface are washed off to obtain a MoS2 / FeS / GF electrode, which is recorded as MoS2 / FeS / GF (0.5).
[0043] Example 3: Preparation of MoS2 / FeS / GF electrode
[0044] The MoS2 / FeS / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:Fe is 1:1.0. The preparation method is as follows:
[0045] S1: Add 2.780g of FeSO4·7H2O and 1.77g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 3.81g CN2H4S and 0.35g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate, and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0046] The other steps are the same as those in Example 1. After naturally cooling to room temperature, the GF after the reaction in the reactor is taken out from the reactor, and the excess catalytic components on the surface are washed off, which is recorded as MoS2 / FeS / GF (1.0).
[0047] Example 4: Preparation of MoS2 / FeS / GF Electrode
[0048] The MoS2 / FeS / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:Fe is 1:0.1. The preparation method is as follows:
[0049] S1: Add 0.278g of FeSO4·7H2O and 1.77g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 3.81g CN2H4S and 0.35g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1 by adding 4.97 g of anhydrous sodium sulfate, and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0050] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and clean them by ultrasonic cleaning for 10 min, and dry them in air at 60 °C to complete the pretreatment of GF;
[0051] The composite catalytic component precursor solution obtained in step S1 was transferred to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and a piece of pretreated GF was placed against the wall; the reactor was sealed and placed in an oven at 3°C·min -1 The temperature was raised to 220°C at a heating rate of 1.50 °C and maintained for 14 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / FeS / GF electrode.
[0052] Example 5: Preparation of MoS2 / FeS / GF Electrode
[0053] The MoS2 / FeS / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:Fe is 1:0.1. The preparation method is as follows:
[0054] S1: Add 0.278g of FeSO4·7H2O and 1.77g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 3.81g CN2H4S and 0.35g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1The solution was adjusted to pH 3 by adding 4.97 g of anhydrous sodium sulfate, and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0055] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and clean them by ultrasonic cleaning for 10 min, and dry them in air at 60 °C to complete the pretreatment of GF;
[0056] The composite catalytic component precursor solution obtained in step S1 was transferred to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and a piece of pretreated GF was placed against the wall; the reactor was sealed and placed in an oven at 5°C·min -1 The temperature was raised to 180°C at a heating rate of 1.50°C and maintained for 14 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / FeS / GF electrode.
[0057] Example 6: Preparation of MoS2 / WO3 / GF electrode
[0058] The MoS2 / WO3 / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:W (the same below) is 7:2.5. The specific preparation method is as follows:
[0059] S1: Add 2.31g of Na2WO4·2H2O and 3.57g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 7.46g CN2H4S and 0.67g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0060] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and ultrasonically clean them for 10 min, and dry them in air at 60°C to complete the pretreatment of GF; transfer the composite catalytic component precursor solution obtained in step S1 to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and place a piece of pretreated GF against the wall; seal the reactor, place it in an oven, and heat it at 5°C·min -1 The temperature was raised to 200°C at a rate of 1.50 °C and maintained for 12 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / WO3 / GF electrode, which was recorded as MoS2 / WO3 / GF (2.5).
[0061] Example 7: Preparation of MoS2 / WO3 / GF electrode
[0062] The MoS2 / WO3 / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:W (the same below) is 7:0.5. The specific preparation method is as follows:
[0063] S1: Add 0.46g of Na2WO4·2H2O and 3.57g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 7.46g CN2H4S and 0.67g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0064] The other steps are the same as those in Example 6. After naturally cooling to room temperature, the GF after the reaction in the reactor is taken out and the excess catalytic components on the surface are washed off to obtain a MoS2 / WO3 / GF electrode, which is recorded as MoS2 / WO3 / GF (0.5).
[0065] Example 8: Preparation of MoS2 / WO3 / GF electrode
[0066] The MoS2 / WO3 / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the atomic molar ratio of Mo:W (the same below) is 7:5.0. The specific preparation method is as follows:
[0067] S1: Add 4.62g of Na2WO4·2H2O and 3.57g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 7.46g CN2H4S and 0.67g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.5 by adding 4.97 g of anhydrous sodium sulfate and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0068] The other steps were the same as those in Example 6. After naturally cooling to room temperature, the GF after the reaction in the reactor was taken out, and the excess catalytic components on the surface were washed off. The GF was recorded as MoS2 / WO3 / GF (5.0).
[0069] Example 9 Preparation of MoS2 / WO3 / GF Electrode
[0070] The MoS2 / WO3 / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the specific preparation method is as follows:
[0071] S1: Add 2.31g of Na2WO4·2H2O and 3.57g of (NH4)6Mo7O into a beaker.24 ·4H2O, 7.46g CN2H4S and 0.67g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 3 by adding 4.97 g of anhydrous sodium sulfate, and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0072] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and ultrasonically clean them for 10 min, and dry them in air at 60°C to complete the pretreatment of GF; transfer the composite catalytic component precursor solution obtained in step S1 to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and place a piece of pretreated GF against the wall; seal the reactor, place it in an oven, and heat it at 5°C·min -1 The temperature was raised to 220°C at a rate of 1.50°C and maintained for 12 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / WO3 / GF electrode.
[0073] Example 10 Preparation of MoS2 / WO3 / GF Electrode
[0074] The MoS2 / WO3 / GF electrode prepared in this embodiment uses graphite felt (GF) as a substrate, and the specific preparation method is as follows:
[0075] S1: Add 2.31g of Na2WO4·2H2O and 3.57g of (NH4)6Mo7O into a beaker. 24 ·4H2O, 7.46g CN2H4S and 0.67g CH4N2O were dissolved in 70mL ultrapure water and 2.0mol L -1 The solution was adjusted to pH 1.0 by adding 4.97 g of anhydrous sodium sulfate, and stirred for more than 10 min to obtain a composite catalytic component precursor solution;
[0076] S2: Cut graphite felt (GF) into sheets of 10 cm × 6 cm, soak them in acetone, ethanol, and ultrapure water in sequence, and ultrasonically clean them for 10 min, and dry them in air at 60°C to complete the pretreatment of GF; transfer the composite catalytic component precursor solution obtained in step S1 to a polytetrafluoroethylene-lined hydrothermal reactor with a capacity of 100 mL, and place a piece of pretreated GF against the wall; seal the reactor, place it in an oven, and heat it at 3°C·min -1 The temperature was raised to 180°C at a rate of 100 °C and maintained for 14 h. After cooling naturally to room temperature, the GF after the reaction in the reactor was taken out and the excess catalytic components on the surface were washed off to obtain the MoS2 / WO3 / GF electrode.
[0077] Preparation of MoS2 / GF Electrode in Comparative Example 1
[0078] The specific preparation method is as follows:
[0079] S1: Add 3.57 g of (NH4)6Mo7O 24 ·4H2O, 7.46 g of CN2H4S, and 0.67 g of CH4N2O into a beaker, dissolve them in 70 mL of ultrapure water, adjust the pH of the solution to 1.5 with 2.0 mol L -1 sulfuric acid, add 4.97 g of anhydrous sodium sulfate, and stir for more than 10 min to obtain a MoS2 precursor solution;
[0080] S2: Cut the graphite felt (GF) into pieces with a size of 10 cm × 6 cm, soak it in acetone, ethanol, and ultrapure water in sequence and ultrasonically clean it for 10 min, and dry it in air at 60 °C to complete the pretreatment of GF; transfer the MoS2 precursor solution obtained in step S1 to a polytetrafluoroethylene-lined hydrothermal reaction kettle with a capacity of 100 mL, and stick a piece of pretreated GF to the wall of the kettle; seal the reaction kettle and place it in an oven, heat it to 200 °C at a heating rate of 5 °C·min -1 and maintain it for 12 h. After naturally cooling to room temperature, take out the GF after the reaction in the reaction kettle and wash off the excess catalytic components on the surface to obtain the MoS2 / GF electrode.
[0081] Next, the performance of the electrodes prepared in the above examples was detected
[0082] <Electrocatalytic Performance Test of MoS2 / FeS / GF Electrode>
[0083] As Figure 1 shown are the cyclic voltammetry curves and galvanostatic charge-discharge curves of MoS2 / FeS / GF(0.1) prepared in Example 1 and the cyclic voltammetry curves of the unmodified GF electrode. From Figure 1 it can be seen that the MoS2 / FeS / GF electrode has both excellent capacitance and electrocatalytic activity, and the electrocatalytic performance of the MoS2 / FeS / GF electrode is more significantly improved compared with the unmodified GF electrode.
[0084] <Selective Removal of Cu in Water by MoS2 / FeS / GF Electrode 2+ >
[0085] A capacitive deionization system with an internal volume of 116 mL and a current collector of carbon paper was used as a reactor. MoS2 / FeS / GF (0.1), MoS2 / FeS / GF (0.5), MoS2 / FeS / GF (1.0) prepared in Examples 1-3, MoS2 / GF prepared in Comparative Example 1, and unmodified GF were used as cathodes, and unmodified GF was used as anode. In the circulating inlet and outlet water mode, the Cu2+ / -2-hydroxy ... 2+ Coexistence of Ni 2+ As an interference, the integrated capacitance electrode was tested for Cu 2+ The selective removal performance of Cu 2+ and Ni 2+ The initial concentration of the water was 30 mg / L, the total volume of the water inlet was 200 mL, and the circulating inlet / outlet flow rate was 30 mL min -1 , the applied voltage is constant at 1.0V, and the test time is 4h.
[0086] It should be noted that in the above test experiment, the unmodified GF used is commercially available graphite felt, which is cut into 10 cm × 6 cm sheets in this test method, soaked in acetone, ethanol, and ultrapure water in turn and ultrasonically cleaned for 10 minutes, and then dried in air at 60°C.
[0087] Some of the test results are as follows Figure 2 As shown in the figure, the MoS2 / FeS / GF cathode with Mo:Fe=1:0.1-1 has a strong conductivity over Cu2+ in 4h. 2+ The removal rate of Ni 2+ 36% higher, showing excellent Cu 2+ Selectivity; MoS2 / FeS / GF cathode with Mo:Fe=1:0.5 has a selectivity to Cu 2+ The removal rate is 77.2%, which is higher than Ni 2+ About 70% higher.
[0088] In contrast, within 4 h, when the unmodified GF was used as the cathode, the system 2+ The removal rate of Ni is 25%. 2+ The removal rate of Cu was 16% when MoS2 / GF was used as cathode. 2+ The removal rate of Ni is 39%. 2+ The removal rate is 23%, which is not only unable to achieve Cu 2+ 、Ni 2+ In the coexistence environment, Cu 2+ or Ni 2+ effective removal of Cu 2+ Therefore, only the modified graphite felt composite electrode of the present invention can achieve Cu 2+ Highly efficient and selective removal.
[0089] <Capacitive and Photoelectrocatalytic Performance Tests of MoS2 / WO3 / GF Electrodes>
[0090] As Figure 3 shown are the cyclic voltammetry curves of MoS2 / WO3 / GF(2.5) and unmodified GF electrodes (inset (a) is the galvanostatic charge-discharge curve of MoS2 / WO3 / GF(2.5); inset (b) is the light absorption performance of the catalytic active components). From Figure 3 it can be seen that the in-situ loading of MoS2 / WO3 on the surface of GF significantly improves the electrocatalytic activity and capacitive performance of the porous carbon electrode; at the same time, the excellent light absorption performance of MoS2 / WO3 endows the electrode with visible light photocatalytic potential. Therefore, the MoS2 / WO3 / GF electrode combines capacitive and photocatalytic and electrocatalytic activities, and can in-situ achieve the efficient integration of capacitive deionization and photoelectrocatalysis. After comparison, MoS2 / WO3 / GF electrodes with Mo:W = 7:0.5 - 5.0 all have similar performance, and among them, MoS2 / WO3 / GF(2.5) has the best comprehensive performance.
[0091] <Removal of Cu in Water by MoS2 / WO3 / GF Electrodes> 2+ <Removal>
[0092] To test the performance of MoS2 / WO3 / GF electrodes in enhancing the removal of Cu 2+ in water, the following two groups of test experiments were carried out:
[0093] Test Experiment 1
[0094] Using a capacitive deionization system with an internal volume of 116 mL and a current collector of carbon paper as the reactor, MoS2 / WO3 / GF(0.5), MoS2 / WO3 / GF(2.5), MoS2 / WO3 / GF(5.0) prepared in Examples 6 - 8, MoS2 / GF prepared in Comparative Example 1, and unmodified GF were used as the cathode, and unmodified GF was used as the anode. In the cyclic inflow and outflow mode, Ni 2+ that often coexists with Cu 2+ in electroplating and smelting wastewater was used as an interference substance to test the selective removal performance of the integrated capacitive electrode for Cu 2+ in water. The initial concentrations of Cu 2+ and Ni 2+ were both 30 mg / L, the total volume of the influent was 200 mL, the cyclic inflow / outflow rate was 30 mL·min -1 , the applied voltage was kept constant at 1.0 V, and the test time was 6 h.
[0095] It should be noted that in the above test experiment, the unmodified GF used is commercially available graphite felt, which is cut into 10 cm × 6 cm sheets in this test method, soaked in acetone, ethanol, and ultrapure water in turn and ultrasonically cleaned for 10 minutes, and then dried in air at 60°C.
[0096] The test results are as follows Figure 4 As shown, the MoS2 / WO3 / GF(2.5) electrode can also be used on Ni 2+ Preferential removal of Cu under interference 2+ , which has a great influence on Cu 2+ The removal rate is higher than that of Ni 2+ 37.2% higher, indicating that Cu 2+ Therefore, the MoS2 / WO3 / GF electrode has both capacitive, photo / electrocatalytic activity and Cu 2+ Selective.
[0097] In contrast, within 6 h, when the unmodified GF was used as the cathode, the system 2+ The removal rate of Ni 2+ The removal rate is 19%. When MoS2 / GF is used as cathode, the system has a good removal rate of Cu 2+ The removal rate is 40%, Ni 2+ The removal rate is 27%, which is not only unable to achieve Cu 2+ 、Ni 2+ In the coexistence environment, Cu 2+ or Ni 2+ effective removal of Cu 2+ Therefore, only the modified graphite felt composite electrode of the present invention can achieve Cu 2+ Highly efficient and selective removal.
[0098] Test 2
[0099] The overall steps of test 2 are the same as those of test 1, except that this test is only used to test the removal of a single Cu 2+ The effect of Ni 2+ Removal rate during interference.
[0100] Specifically: A capacitive deionization system with an internal volume of 116 mL and a current collector of carbon paper was used as a reactor, and MoS2 / WO3 / GF (0.5), MoS2 / WO3 / GF (2.5), MoS2 / WO3 / GF (5.0) and unmodified GF prepared in Examples 6-8 were used as cathodes, and unmodified GF was used as anode. In the circulating water inlet and outlet mode, the integrated capacitive electrode was tested for Cu in water. 2+ The selective removal performance of Cu 2+The initial concentration of the water was 30 mg / L, the total volume of the water inlet was 200 mL, and the circulating inlet / outlet flow rate was 30 mL min -1 , the applied voltage is constant at 1.0V, and the test time is 8h.
[0101] The results are as follows Figure 5 As shown in the figure, MoS2 / WO3 / GF electrodes with Mo:W ratios of 7:0.5, 7:2.5, and 7:5.0 can enhance the 2+ Removal of Cu within 8 hours 2+ The removal rates were 40.4%, 63.0% and 35.7% higher than those of unmodified GF, respectively.
[0102] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a capacitive catalytic electrode for selective removal of copper ions, characterized in that: The following steps are involved: S1: dissolving ammonium molybdate tetrahydrate, thiourea, urea and tungstate or ferrous salt in water, adjusting the solution pH to 1.0-3.0, then adding sodium sulfate and stirring to obtain a composite catalytic component precursor solution; S2: Immerse the porous carbon substrate in the composite catalyst component precursor solution, and then heat the composite catalyst component precursor solution at a temperature not exceeding 5°C / min. -1 The temperature is raised to 180-220° C. at a heating rate of 1000 ℃ and kept at this temperature for 12-14 hours. After cooling, the porous carbon substrate is taken out and cleaned to obtain the capacitive catalytic electrode.
2. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: In the composite catalytic component precursor solution, the atomic molar ratio of Mo:W is 7:0.5-5.0, or the atomic molar ratio of Mo:Fe is 1:0.1-1.
0.
3. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: The tungstate is sodium tungstate or sodium tungstate hydrate, and the ferrous salt is ferrous sulfate or ferrous sulfate hydrate.
4. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: In step S1, 2.0 mol L -1 The pH of the solution was adjusted to 1.0-3.0 with sulfuric acid.
5. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: The porous carbon substrate is pretreated and then immersed in a composite catalytic component precursor solution. The pretreatment process is as follows: the porous carbon substrate is sequentially cleaned and dried in acetone, anhydrous ethanol and ultrapure water, and then cut into a target size.
6. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: The porous carbon substrate is graphite felt, activated carbon felt, carbon fiber cloth or activated carbon particles.
7. The method for preparing a capacitive catalytic electrode for selective removal of copper ions according to claim 1, characterized in that: Porous carbon substrates are two-dimensional or three-dimensional carbon materials with capacitive properties.
8. A capacitive catalytic electrode for selective removal of copper ions, characterized in that: Prepared by the method described in any one of claims 1 to 7, the capacitive catalytic electrode is a MoS2 / FeS / GF electrode or a MoS2 / WO3 / GF electrode.
9. Use of the capacitive catalytic electrode for selective removal of copper ions as claimed in claim 8 in treating industrial wastewater.
10. Use of the capacitive catalytic electrode for selective removal of copper ions according to claim 9 in treating industrial wastewater, characterized in that: The industrial sewage is industrial sewage containing copper and nickel.
Citation Information
Patent Citations
Preparation method of ferric molybdate (II) / graphene oxide catalytic electrode
CN108821394A
Novel electrocatalytic hydrogen evolution electrode preparation method
CN110184615A
Fuel cell treatment method for wastewater containing copper complex
CN116282389A
Treating method for bleached pulp that uses reducing bleaching agent
JP2011256485A
Robust flow-through platform for organic contaminants removal
US20210155514A1
